2003
DOI: 10.1111/j.1442-200x.2003.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass immunization against influenza encephalopathy on mortality rates in children

Abstract: The results of the present study suggest that mass immunization of school-aged children reduced the mortality rate from influenza-associated acute encephalopathy/encephalitis in children less than 9 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…Accordingly, fatal cases of encephalopathy may have significantly contributed to the increase in the number of excess deaths observed among young children, although prominent numbers of excess all-cause deaths have been noted since 1990. The authors of one report hypothesized that the discontinuation of mass vaccination of schoolchildren was responsible for the increase in the incidence of influenza-associated encephalopathy [20], and our results appear to support this hypothesis.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, fatal cases of encephalopathy may have significantly contributed to the increase in the number of excess deaths observed among young children, although prominent numbers of excess all-cause deaths have been noted since 1990. The authors of one report hypothesized that the discontinuation of mass vaccination of schoolchildren was responsible for the increase in the incidence of influenza-associated encephalopathy [20], and our results appear to support this hypothesis.…”
Section: Discussionsupporting
confidence: 86%
“…For seasonal influenza, three studies assessed vaccine efficacy in the general population [67]–[69], eight studies in children [68], [70][76], four studies in elderly populations [68], [77][79], two in health care workers [80], [81] and one in immunocompromised haemodialysis patients [82].…”
Section: Resultsmentioning
confidence: 99%
“…However, one study from Japan showed that the mortality rate from IAE in children was significantly lower during the era of mass influenza immunization (pre-1994) than in a subsequent era (1995)(1996)(1997)(1998)(1999)(2000) [20]. Therefore, influenza vaccination, which is recommended in young children and strongly recommended in children with underlying diseases, could avoid influenza-associated complications in our children.…”
Section: Discussionmentioning
confidence: 98%